Social innovation in the commercialization of organic and agroecological products of family farming in Brazil’s Federal District (Sustainability in Debate, 2014)
The Federal District and particularly the city of Brasilia constitute a booming marketfor organic and agro-ecological products. This paper develops a characterization ofthe modes of family farmer’s organization for marketing of organic and agroecologicalproducts in the Federal District of Brasilia. The methodology hasassociated an analysis of documents and statistics and interviews of the variousactors of the two main chains of products in the Federal District: producers of theagro-ecological fairs, farmer’s organizations, supermarkets, extension agents andtechnicians of public agencies. Family farmers have progressively invested the shortfood chains with direct sales and agro-ecological fairs, through specific andinnovative modalities of coordination and organization. The main results show acombination between formal and informal status and institutions and themobilization of renewed forms of reciprocity, mutual help and collective learning.